Gospodarowanie nawozami azotowymi w Europie w kontekście ich wpływu na środowisko = Management of nitrogen fertilizers in Europe in terms of their impact on the environment - Ossowska, Magdalena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The aim of this review is to analyse the tendencies of nitrogen fertilizers use in Europe and evaluation how those trends will affect the natural environment. The main sources of information included reports from the EU institutions and European countries, as well as reviews and research of various research facilities. In the last decades the environmental policies and a high price of fertilizers reduced use of nitrogen fertilizers in the Western Europe, but in comparing to other world regions the N input remains very high.
Keywords: nawozy azotowe; zużycie nawozów; amoniak; oddziaływanie na środowisko; nitrogen fertilizer; fertilizer management; ammonium; air pollution